The development of knowledge audit for knowledge management programs to improve organizational performance - ชำนาญช่าง, กรกฎ (Journal of Business, Innovation and Sustainability (JBIS), 2012)
Knowledge management recognizes as an important driver of organizational performance. And one of the first important steps in the knowledge management programs is to conduct knowledge audit. This paper explains the importance of knowledge audit in enhancing the knowledge management processes. The paper then illustrates the knowledge audit framework to explain the components of knowledge management factors, knowledge audit, knowledge management processes, and organizational performance in the examination. By utilizing the knowledge audit framework, organization will understand the basic contents of knowledge audit and implement an effective knowledge audit to help improve organization performance. DOI: http://dx.doi.org/10.14456/becj.2012.15